2021
DOI: 10.3390/molecules26226945
|View full text |Cite
|
Sign up to set email alerts
|

The Renin-Angiotensin System: A Key Role in SARS-CoV-2-Induced COVID-19

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), was first identified in Eastern Asia (Wuhan, China) in December 2019. The virus then spread to Europe and across all continents where it has led to higher mortality and morbidity, and was declared as a pandemic by the World Health Organization (WHO) in March 2020. Recently, different vaccines have been produced and seem to be more or less effective in protecting from COVID-19. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 153 publications
0
33
0
Order By: Relevance
“…In the cardiovascular system (CV) system, AT1R overactivity has been associated with the development of several pathological conditions, including hypertension, vascular inflammation, atherosclerosis, and heart failure [ 55 , 56 ]. Furthermore, Ang II–AT1R binding activates many cascades in the vasculature, such as protein tyrosine phosphatases, NADPH oxidase, MAPK, and NO synthase, resulting in the expression of proinflammatory mediators, contraction, and endothelial dysfunction [ 57 , 58 ]. When AT1R is stimulated, NF-κB is activated, causing resident cells and endothelial cells to upregulate proinflammatory and procoagulant factors.…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In the cardiovascular system (CV) system, AT1R overactivity has been associated with the development of several pathological conditions, including hypertension, vascular inflammation, atherosclerosis, and heart failure [ 55 , 56 ]. Furthermore, Ang II–AT1R binding activates many cascades in the vasculature, such as protein tyrosine phosphatases, NADPH oxidase, MAPK, and NO synthase, resulting in the expression of proinflammatory mediators, contraction, and endothelial dysfunction [ 57 , 58 ]. When AT1R is stimulated, NF-κB is activated, causing resident cells and endothelial cells to upregulate proinflammatory and procoagulant factors.…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…On the other hand, ACE2 counterbalances Ang II–AT1R effects by either stimulating an alternative pathway for Ang I degradation to produce Ang-(1–9), or by inactivating Ang II and hydrolyzing it to a heptapeptide Ang-(1–7). The latter stimulates vasodilation and activates anti-inflammatory, antifibrotic, and antithrombotic cascades via the MasR axis [ 59 , 60 ], as well as the protection of endothelial cell activity [ 57 , 58 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…Several studies have shown considerable association between ACE genotype (as observed with variable prevalence in different ethnic populations) and various disease endpoints such as sepsis, ARDS ( Pabalan et al, 2021 ), and risk of pneumonia ( Nie et al, 2014 ). In the context of COVID-19, there may also be a connection between frequency of ACE genotypes in populations and severity and outcome of this disease ( El-Arif et al, 2021 ). Furthermore, single-nucleotide polymorphisms in the ACE2 gene on chromosome Xp22.2 have been discussed as possible predetermining factors for COVID-19 severity.…”
Section: The Renin-angiotensin System In Covid-19mentioning
confidence: 99%
“…The best-characterized ACE2 polymorphism is the splice region variant (rs2285666, G > A, Intron 3/4), which has also been shown to be associated with hypertension, coronary heart disease and diabetes with cerebral stroke ( Mohlendick et al, 2021 ). Other ACE2 polymorphisms may affect ACE2-spike protein binding affinity or binding of the co-factor TMPRSS2 that is needed for viral cell entry ( El-Arif et al, 2021 ; Suryamohan et al, 2021 ). In a study including hospitalized patients with COVID-19 age, high soluble ACE2 levels, a low aldosterone to renin ratio and the TMPRSS2 rs2070788 non-AA genotype were factors that independently predicted disease severity ( Akin et al, 2021 ).…”
Section: The Renin-angiotensin System In Covid-19mentioning
confidence: 99%
“…SARS-CoV-2 decreases the effects of bradykinin 2-receptor as it affects bradykinin synthesis by inhibiting cathepsin L, present at the site of infection and involved in bradykinin production. Dysregulation of the renin-angiotensin-aldosterone balance and overactivation of angiotensin II type-I receptor axis could result in vasoconstriction and induction of the pro-fibrotic, apoptotic, and inflammatory signalizations in SARS-CoV-2-targeted tissues [21].…”
mentioning
confidence: 99%